Arts-Based Compassion Skills Training (ABCST): Channelling Compassion Focused Therapy Through Visual Arts for Australia’s Indigenous Peoples - Bennett-Levy, James; Roxburgh, Natalie; Hibner, Lia; Bala, Sunita; Edwards, Stacey; Lucre, Kate; Cohen, Georgina; O’Connor, Dwayne; Keogh, Sharmaine; Gilbert, Paul (Frontiers in Psychology, 2020)
The last 20 years have seen the development of a new form of therapy, compassion focused therapy (CFT). Although CFT has a growing evidence base, there have been few studies of CFT outside of an Anglo-European cultural context. In this paper, we ask: Might a CFT-based approach be of value for Indigenous Australians? If so, what kind of cultural adaptations might be needed? We report the findings from a pilot study of an arts-based compassion skills training (ABCST) group, in which usual CFT group processes were significantly adapted to meet the needs of Indigenous Australians. At face value, CFT appeared to be a promising approach to enhancing the social and emotional wellbeing of Australia’s Indigenous peoples. However, despite initial consultations with Indigenous health professionals, the first attempts to offer a more conventional group-based CFT to Indigenous clients were largely unsuccessful. Following a review and advice from two Indigenous clients, we combined elements of CFT with visual arts to develop a new approach, “arts-based compassion skills training” (ABCST). This paper reports an evaluation of this pilot ABCST group. The group had 6 x 4 hour sessions of ABCST, facilitated by two psychologists (1 Indigenous, 1 non-Indigenous) and two artists (1 Indigenous, 1 non-Indigenous). There were ten participants, who attended for between 2 and 6 sessions: five were clients, five were health professionals. Between one and three months later, six of the participants (2 clients, 4 health professionals) were interviewed. Qualitative analysis of interview data identified that two key processes - creating a positive group atmosphere and channelling CST through the medium of visual arts - led to four positive outcomes for participants: (1) Planting the seeds of new understandings, (2) embodying the skills of compassion, (3) strengthening relationships with others, and (4) evolving a more self-compassionate relationship. We suggest that the preliminary results are sufficiently encouraging to warrant further development of ABCST in Indigenous communities.